Implementasi Keterampilan Guru Memberi Penguatan Dalam Proses Pembelajaran di Sekolah Dasar - Bekata, Halena M.; Dony, Petrus Mau Tellu; Daik, Triznawasti Y.; Mata, Yessy; Saetban, Antonius A.; Fanpada, Nehemia; Wabang, Yermia Semuel (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the implementation of teacher skills to strengthen the learning process in elementary schools. The skill of holding variations and providing reinforcement are two important aspects in improving the quality of learning, which can affect students' motivation and learning outcomes. The method used in this study is a qualitative descriptive approach with observation and interviews as data collection techniques. The results of the study show that the application of the skill of holding variations, such as changes in learning methods, media, and resources, is able to create a more interesting and interactive learning atmosphere. In addition, the strengthening skills carried out by teachers, both in the form of positive and negative reinforcement, can increase students' enthusiasm for learning and strengthen their understanding of the material. This study shows that 71.7% of students rated the variation of the teacher's voice style very well, while 84.9% of students rated the variety of learning strategies as also very good. Verbal reinforcement was rated positive by 78.2% of students, and non-verbal reinforcement received a good rating with a percentage between 47.3% to 70.9%. These findings show the importance of teachers continuing to develop variations in teaching and reinforcement techniques to increase student motivation and engagement. Based on the results of this study, it can be concluded that the skill of strengthening teachers in the form of positive and negative values increases students' interest in learning in the learning process at school.